Enhancing Capacity in Scaling Community-Based Breeding Programs for Development Partners and Communities in Different Regions of Ethiopia - Getachew, Tesfaye; Belay, Berhanu; Haile, Aynalem (International Center for Agricultural Research in the Dry Areas, 2023)
Since 2009, Community-based Breeding Programs (CBBPs) have been successfully implemented in Ethiopia, resulting in significant genetic advancements for the selected traits within the program.